Screening of Natural Compounds as Activators of the Keap1-Nrf2 Pathway - Wu, Kai C.; McDonald, Peter R.; Liu, Jie; Klaassen, Curtis D. (Planta Medica, 2014)
Nuclear factor erythroid 2-related factor 2 is a master regulator that promotes transcription of cytoprotective genes in response to oxidative/electrophilic stress. A large number of natural dietary compounds are thought to protect against oxidative stress, and a few have been reported to induce genes involved in antioxidant defense through activating nuclear factor erythroid 2-related factor 2. Therefore, a library of 54 natural compounds were collected to determine whether they are nuclear factor erythroid 2-related factor 2 activators and to compare their efficacy and potency to activate nuclear factor erythroid 2-related factor 2. The assay utilized AREc32 cells that contain a luciferase gene under the control of antioxidant response element promoters. Each natural compound was tested at 13 concentrations between 0.02 and 30 µM. Known nuclear factor erythroid 2-related factor 2 activators tert-butylhydroquinone and 2-cyano-3,12-dioxooleana-1,9-diene-28-imidazolide were used as positive controls in parallel with the natural compounds. Among the 54 tested natural compounds, andrographolide had the highest efficacy, followed by trans-chalcone, sulforaphane, curcumin, flavone, kahweol, and carnosol, all of which had better efficacy than tert-butylhydroquinone. Among the compounds tested, 2-cyano-3,12-dioxooleana-1,9-diene-28-imidazolide was the most potent, having an EC50 of 0.41 µM. Seven of the natural compounds, namely andrographolide, trans-chalcone, sulforaphane, curcumin, flavone, kahweol, and cafestol had lower EC50 values than tert-butylhydroquinone but higher than 2-cyano-3,12-dioxooleana-1,9-diene-28-imidazolide. The present study provides insights into which natural compounds activate the Keap1-nuclear factor erythroid 2-related factor 2 pathway and thus might be useful for detoxifying oxidative/electrophilic stress.
Keywords: Nrf2; natural compounds; oxidative stress